Die Reculées des Mittleren Französischen Plateaujura - Zeese, Reinhard (ERDKUNDE, 1977)
The reculées of the Central French Plateau Jura are presented as polygenetic forms, the present appearance of which cannot be explained by recent processes. They experienced their last intensive imprint from glaciers of the pre-Würm period. The further deepening and steepening of the valley resulting from this is responsible for the subsequent dynamics including recent slips and landslides. The original formation definitely already occurred during the Tertiary, and thus under climatic conditions that differ from the present ones. It is therefore not possible to develop conceptual models in the French Jura which would be generally applicable to elucidation of the cul-de-sac valleys. They are localized special forms.